Oxidation of Elemental Sulfur to Thiosulfate by Streptomyces - Yagi, Sigeo (1971)
Streptomyces sioyaensis, which produces the antibiotic siomycin, oxidizes elemental sulfur when added to the culture medium and accumulates thiosulfate in the fermented broth. The accumulated thiosulfate was isolated as the ammonium salt and was identified by melting point, IR spectrum, and paper chromatography. A variety of other streptomycetes also oxidized elemental sulfur and accumulated thiosulfate.